2023
DOI: 10.1186/s12978-023-01627-7
|View full text |Cite
|
Sign up to set email alerts
|

Traditional supports and contemporary disrupters of high fertility desires in sub-Saharan Africa: a scoping review

Abstract: Rationale The desired number of children is markedly higher in Sub-Saharan Africa (SSA) than in other major regions. Efforts to understand how and why these desires are generated and maintained have yielded a broad research literature. Yet there is no full picture of the range of contextual, cultural, and economic factors that support and disrupt high fertility desires. Objective This scoping review synthesizes thirty years of research on the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…However, differences in outcome variable measurement, study period, sample size, and categories of the outcome variable might be related to the study setting. Existing conditions, such as differences in sociocultural norms and expectations regarding family size, differences in economic conditions, government policies related to family planning, and disparities in access to contraception services and health care infrastructure, may also contribute to these differences [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in outcome variable measurement, study period, sample size, and categories of the outcome variable might be related to the study setting. Existing conditions, such as differences in sociocultural norms and expectations regarding family size, differences in economic conditions, government policies related to family planning, and disparities in access to contraception services and health care infrastructure, may also contribute to these differences [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, women in the rich and very rich quintiles may be better educated than those in the poorer groups. Given the strong link between education level and desire for children (negative association between formal schooling and desired fertility) [35,36], they could, therefore, space births better than poor women. However, a study in Ethiopia showed that poor households were less likely than wealthy households to have a short birth interval [37].…”
Section: Discussionmentioning
confidence: 99%
“…There is extensive discussion in traditional gender theories regarding the role that gender plays in decision-making and behavior across cultures and nationalities, particularly in Africa (Olatunji, 2013 ; Olonade et al, 2021 ). Patriarchal norms and gender roles perpetuated by patriarchal institutions favor male children (Sylvia, 1989 ; Church et al, 2023 ; Ibrahim et al, 2023 ). A high priority is given to continuing a family lineage through male children in Nigeria (Church et al, 2023 ).…”
Section: Current Studymentioning
confidence: 99%
“…Patriarchal norms and gender roles perpetuated by patriarchal institutions favor male children (Sylvia, 1989 ; Church et al, 2023 ; Ibrahim et al, 2023 ). A high priority is given to continuing a family lineage through male children in Nigeria (Church et al, 2023 ). Women have traditionally been assigned the role of household and caregiving (Ibrahim et al, 2023 ), while men have traditionally been assigned the role of breadwinner (Mensah, 2023 ).…”
Section: Current Studymentioning
confidence: 99%